Sustainable Governance to Improve the Performance of SOEs Bank Listed on Indonesian Stock Exchange that are Classified as LQ45 - Mochamad Muslih; Dahlia Banjarnahor (Majalah Ilmiah Bijak, 2020)
Corporate governance is useful for improving company performance. Company performance can be in the form of financial performance or non-financial performance. In this digital era, the role of governance is very important. One of the elements of governance is information technology governance. The purpose of this research is to study the effect of corporate governance on the performance of the State-Owned Banks listed on the Indonesia Stock Exchange which is classified as LQ 45. The research method is quantitative method. The 3 (three) governance variables used in this study are commissioners compensation, board size, and audit committee size. The population is state-owned banking sector companies listed on the Indonesia Stock Exchange classified as LQ 45.